[Erratum] FTIR Spectroscopic and Theoretical Study of the Photochemistry of Matrix-isolated Coumarin - Kus, Nihal (2007)
A correction to the article "FTIR Spectroscopic and Theoretical Study of the Photochemistry of Matrix-isolated Coumarin" that was published in the previous issue is presented..